2021
DOI: 10.1091/mbc.e20-10-0680
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeleton integrity influences XRCC1 and PCNA dynamics at DNA damage

Abstract: Upon induction of DNA damage with 405 nm laser light, proteins involved in Base Excision Repair (BER) are recruited to DNA lesions. We find that the dynamics of factors typical of either short-patch (XRCC1) or long-patch (PCNA) BER are altered by chemicals that perturb actin or tubulin polymerization in human cells. Whereas the destabilization of actin filaments by Latrunculin B, Cytochalasin B or Jasplakinolide decreases BER factor accumulation at laser-induced damage, inhibition of tubulin polymerization by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 60 publications
2
8
0
Order By: Relevance
“…To further confirm this point, we performed in situ DNA digestion and observed that control cells were more sensitive to DNA digestion (visualized as a reduction in the nuclear area by DNAse activity) than MA cells (Figure S6G). Finally, several reports show that actin cytoskeleton is required during DNA damage response [36,37]. We investigated the levels of γH2AX in MA cells treated with latrunculin and jasplakinolide, and found that γH2AX were reduced in MA cells treated with latrunculin, whereas jasplakinolide treatment exhibited a more similar phenotype to untreated MA cells (Figures 6F, and 6G).…”
Section: Actin Homeostasis Controls Lamin B1 Redistribution and The N...mentioning
confidence: 81%
“…To further confirm this point, we performed in situ DNA digestion and observed that control cells were more sensitive to DNA digestion (visualized as a reduction in the nuclear area by DNAse activity) than MA cells (Figure S6G). Finally, several reports show that actin cytoskeleton is required during DNA damage response [36,37]. We investigated the levels of γH2AX in MA cells treated with latrunculin and jasplakinolide, and found that γH2AX were reduced in MA cells treated with latrunculin, whereas jasplakinolide treatment exhibited a more similar phenotype to untreated MA cells (Figures 6F, and 6G).…”
Section: Actin Homeostasis Controls Lamin B1 Redistribution and The N...mentioning
confidence: 81%
“…Many studies have reported that they are significantly correlated with prognosis in different cancer types, such as colorectal cancer, pancreatic cancer, gastric cancer, and so on ( Luo et al, 2018 ; Zhang et al, 2019 ; Li et al, 2021 ). NEIL3 , PCNA , RFC3 , and POLD2 play important roles in the BER pathway which are recruited to DNA lesions and cleave and repair the damaged bases cooperatively ( Robertson et al, 2009 ; Hurst et al, 2021 ; Wang et al, 2021 ). Zhao et al found that NEIL3 activated cell cycle progression, leading to poor prognosis ( Zhao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, at first stage of ODD, the PCNA in cooperation with BER enzymes (mainly glycosylases), initiates the repairing process. Thus, failure of this system ends up with expanded DNA damage in the testicular cellularity (Hurst et al, 2021; Moradi‐Ozarlou et al, 2021; Moshari et al, 2017; Tsai et al, 2017). Therefore, the METH‐suppressed PCNA expression might negatively affect BER enzyme expression.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, proliferating cell nuclear antigen (PCNA) is a member of the sliding clamp family, which involves as a proceeding element in the polymerase process (Moradi-Ozarlou et al, 2021;Moshari et al, 2017) and is reported to promote the BER enzymes-induced roles in the DNA repairing process. In line with this issue, it has shown that the PCNA plays a crucial role in interacting with almost all players in the BER process, including glycosylases, AP endonuclease, and XRCC1 (Hurst et al, 2021;Tsai et al, 2017). As a matter of fact, the BER pathway removes the DNA lesions mainly after ODD, which is divided into different stages of detection and cutting, incision, replacement, processing of DNA terminals, and DNA sealing (Hu et al, 2021).…”
mentioning
confidence: 94%